Improving of electromechanical servo systems accuracy - Kuznetsov, B.I.; Nikitina, T.B.; Kolomiets, V.V.; Bovdui, I.V. (Електротехніка і електромеханіка, 2018)
Aim. Improving of accuracy parameters and reducing of sensitivity to changes of plant parameters of nonlinear robust
electromechanical servo systems of guidance and stabilization of lightly armored vehicle weapons based on multiobjective
synthesis. Methodology. The method of multicriterion synthesis of nonlinear robust controllers for controlling by nonlinear
multimass electromechanical servo systems with parametric uncertainty based on the choice of the target vector of robust control
by solving the corresponding multicriterion nonlinear programming problem in which the calculation of the vectors of the
objective function and constraints is algorithmic and associated with synthesis of nonlinear robust controllers and modeling of
the synthesized system for various modes of operation of the system, with different input signals and for various values of the
plant parameters. Synthesis of nonlinear robust controllers and non-linear robust observers reduces to solving the system of
Hamilton-Jacobi-Isaacs equations. Results. The results of the synthesis of a nonlinear robust electromechanical servo system for
the guidance and stabilization of lightly armored vehicle weapons are presented. Comparison of the dynamic characteristics of
the synthesized servo electromechanical system showed that the use of synthesized nonlinear robust controllers allowed to
improve the accuracy parameters and reduce the sensitivity of the system to changes of plant parameters in comparison with the
existing system. Originality. For the first time carried out the multiobjective synthesis of nonlinear robust electromechanical servo
systems of guidance and stabilization of lightly armored vehicle weapons. Practical value. Practical recommendations are given
on reasonable choice of the gain matrix for the nonlinear feedbacks of the regulator and the nonlinear observer of the servo
electromechanical system, which allows improving the dynamic characteristics and reducing the sensitivity of the system to plant
parameters changing in comparison with the existing system. Цель. Повышение параметров точности и уменьшение чувствительности системы к изменениям параметров
объекта управления нелинейной робастной электромеханической следящей системы наведения и стабилизации
вооружения легкобронированной машины на основе многокритериального синтеза. Методология. Метод
многокритериального синтеза нелинейных робастных регуляторов для управления нелинейными многомассовыми
электромеханическими следящими системами с параметрической неопределенностью основан на выборе вектора
цели робастного управления путем решения соответствующей задачи многокритериального нелинейного
программирования, в которой вычисление векторов целевой функции и ограничений носит алгоритмический
характер и связано с синтезом нелинейных робастных регуляторов и моделированием синтезированной системы для
различных режимов работы системы, при различных входных сигналах и для различных значений параметров
объекта управления. Синтез нелинейных робастных регуляторов и нелинейных робастных наблюдателей сводится к
решению системы уравнений Гамильтона – Якоби – Айзекса. Результаты. Приводятся результаты синтеза
нелинейной робастной электромеханической следящей системы наведения и стабилизации вооружения
легкобронированной машины. Сравнение динамических характеристик синтезированной следящей
электромеханической системы показало, что применение синтезированных нелинейных робастных регуляторов
позволяет повысить параметры точности и снизить чувствительность системы к изменению параметров объекта
управления по сравнению с существующей системой. Оригинальность. Впервые проведен многокритериальный
синтез нелинейной робастной электромеханической следящей системы наведения и стабилизации вооружения
легкобронированной машины. Практическая ценность. Приводятся практические рекомендации по обоснованному
выбору матриц коэффициентов усиления нелинейных обратных связей регулятора и нелинейного наблюдателя
следящей электромеханической системы, что позволяет улучшить динамические характеристики и снизить
чувствительность системы к изменению параметров объекта управления по сравнению с существующей системой